Non-Test Evaluation Analysis of Teachers and Students on the Room Planner Application in Interior Design - Perwitasari, Wahyu; Rufi’i, Rufi’i (research, training and philanthropy institution Natural Aceh, 2024)
Technology in interior design education is essential for improving the quality of education. Android is a technology that can help students create a unique classroom environment. The aim of this research is to determine user satisfaction levels with the Room Planner application while they are learning about interior design. To understand how users utilize the Room Planner application, five teachers and ten students participated in a survey. User opinions about the application were also examined. The analysis results showed that most educators were happy using the application as an educational tool. The majority of compatibility percentages were